A simple in-host model for Mycobacterium tuberculosis that captures all infection outcomes. Issue 1 (2nd January 2017) - Du, Yimin; Wu, Jianhong; Heffernan, Jane M.
ABSTRACT: Tuberculosis infection can result in clearance, latent infection, or active disease, with slow or fast progression. A four-dimensional model of in-host tuberculosis infection includes macrophages, T lymphocytes, tuberculosis bacteria, and their interactions. Changes in the infection rate, cell-mediated immunity rate, macrophage loss rate, and bacteria killing rate most affect disease outcomes. Simulations show that a periodic solution can occur. When the infected macrophage killing rate is constant, a backward bifurcation exists and the system is globally stable.